Stroke Patients with a Past History of Cancer Are at Increased Risk of Recurrent Stroke and Cardiovascular Mortality - Lau, Kui-Kai; Wong, Yuen-Kwun; Teo, Kay-Cheong; Chang, Richard Shek-Kwan; Hon, Sonny Fong-Kwong; Chan, Koon-Ho; Cheung, Raymond Tak-Fai; Li, Leonard Sheung-Wai; Tse, Hung-Fat; Ho, Shu-Leong; Siu, Chung-Wah (PLOS ONE, 2014)
Background and Purpose Cancer patients are at increased risk of cardiovascular and cerebrovascular events. It is unclear whether cancer confers any additional risk for recurrent stroke or cardiovascular mortality after stroke. Methods This was a single center, observational study of 1,105 consecutive Chinese ischemic stroke patients recruited from a large stroke rehabilitation unit based in Hong Kong. We sought to determine whether patients with cancer are at higher risk of recurrent stroke and cardiovascular mortality. Results Amongst 1,105 patients, 58 patients (5.2%) had cancer, of whom 74% were in remission. After a mean follow-up of 76±18 months, 241 patients developed a recurrent stroke: 22 in patients with cancer (38%, annual incidence 13.94%/year), substantially more than those without cancer (21%, 4.65%/year) (p<0.01). In a Cox regression model, cancer, age and atrial fibrillation were the 3 independent predictors of recurrent stroke with a hazard ratio (HR) of 2.42 (95% confidence interval (CI): 1.54–3.80), 1.01 (1.00–1.03) and 1.35 (1.01–1.82) respectively. Likewise, patients with cancer had a higher cardiovascular mortality compared with those without cancer (4.30%/year vs. 2.35%/year, p = 0.08). In Cox regression analysis, cancer (HR: 2.08, 95% CI: 1.08–4.02), age (HR: 1.04, 95% CI 1.02–1.06), heart failure (HR: 3.06, 95% CI 1.72–5.47) and significant carotid atherosclerosis (HR: 1.55, 95% CI 1.02–2.36) were independent predictors for cardiovascular mortality. Conclusions Stroke patients with a past history of cancer are at increased risk of recurrent stroke and cardiovascular mortality.